2019
DOI: 10.1073/pnas.1908481116
|View full text |Cite
|
Sign up to set email alerts
|

Fluid pumping and active flexoelectricity can promote lumen nucleation in cell assemblies

Abstract: julicher@pks.mpg.de

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
(80 reference statements)
0
39
0
Order By: Relevance
“…To date, a number of theoretical frameworks have been proposed to model lumen growth, focusing either on the early phase of lumen nucleation (see Glossary, Box 1) and coalescence (Dasgupta et al, 2018;Duclut et al, 2019;Dumortier et al, 2019), or on the later phase when the singly resolved lumen undergoes size oscillations (Ruiz-Herrero et al, 2017). A general assumption of these models is that lumen growth is governed by water intake resulting from inward ion transport (for example by sodium-potassium pumps).…”
Section: Lumen Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of theoretical frameworks have been proposed to model lumen growth, focusing either on the early phase of lumen nucleation (see Glossary, Box 1) and coalescence (Dasgupta et al, 2018;Duclut et al, 2019;Dumortier et al, 2019), or on the later phase when the singly resolved lumen undergoes size oscillations (Ruiz-Herrero et al, 2017). A general assumption of these models is that lumen growth is governed by water intake resulting from inward ion transport (for example by sodium-potassium pumps).…”
Section: Lumen Formationmentioning
confidence: 99%
“…However, given recent evidence that the secretion of cytoplasmic vesicles into intercellular space also contributes to microlumina formation (Ryan et al, 2019;Vasquez et al, 2019 preprint), such a mechanism should also be incorporated into future theoretical models. Interestingly, recent theoretical work has shown that ion flows in the fluid can lead to the build up of an electric field across the tissue, the shape of which can, in turn, influence lumen nucleation dynamics and size (Duclut et al, 2019), although this warrants further experimental investigation. Finally, to understand the role of lumen in tissue patterning, future theoretical frameworks must incorporate various feedback interactions between luminal signalling, tissue mechanics and cell fate across multiple spatial and temporal scales.…”
Section: Lumen Formationmentioning
confidence: 99%
“…Lumina expand either isotropically, yielding spherical structures (acini and alveoli in vivo, cysts and organoids in vitro), or anisotropically, generating a variety of epithelial tube shapes across tissues (e.g., lungs, intestine, kidney, and liver). The anisotropic expansion of lumina is more difficult to explain than the isotropic one because it results from specific combinations of molecular pathways and physical forces ( Datta et al, 2011 ; Navis and Nelson, 2016 ; Jewett and Prekeris, 2018 ; Dasgupta et al, 2018 ; Stopka et al, 2019 ; Duclut et al, 2019 ). Physical forces can act on the tissue or cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for such a pattern would be pulse trains (e.g., muscle clonus [ Hidler and Rymer, 2000 ]), which can indeed be observed in organoid contractions, such as the highlighted region of Figure 3 B. Physical fluidic models of lumen contractility have been proposed ( Duclut et al., 2019 ; Ruiz-Herrero et al., 2017 ) but are not sufficient to predict pulse train or other temporally correlated behavior, suggesting that the contractility phenomenon is biomechanical.
Figure 3 Mammary organoids grown in microcontainers exhibit contractility (A) Filmstrips show single contractions of three organoids.
…”
Section: Resultsmentioning
confidence: 99%